Extracellular vesicles biogenesis, isolation, manipulation and genetic engineering for potential in vitro and in vivo therapeutics: An overview - Hadizadeh, Nastaran; Bagheri, Diba; Shamsara, Mehdi; Hamblin, Michael R.; Farmany, Abbas; Xu, Mengdi; Liang, Zhuobin; Razi, Farideh; Hashemi, Ehsan (Frontiers in Bioengineering and Biotechnology, 2022)
The main goals of medicine consist of early detection and effective treatment of different diseases. In this regard, the rise of exosomes as carriers of natural biomarkers has recently attracted a lot of attention and managed to shed more light on the future of early disease diagnosis methods. Here, exosome biogenesis, its role as a biomarker in metabolic disorders, and recent advances in state-of-art technologies for exosome detection and isolation will be reviewed along with future research directions and challenges regarding the manipulation and genetic engineering of exosomes for potential in vitro and in vivo disease diagnosis approaches.